Hybrid process, electrocoagulation-biofiltration for landfill leachate treatment. (May 2018) - Dia, Oumar; Drogui, Patrick; Buelna, Gerardo; Dubé, Rino
Highlights: BF and EC processes were sequentially combined to treat landfill leachate. EC was efficient to remove insoluble COD, phosphorus, color, and metals. BF treatment allowed to totally remove ammonia and BOD. Fractionation of organic matter showed that HA fraction was removed by EC. FA and hydrophilic compounds were removed during the BF. Abstract: Landfill leachates are known for their high and complex composition of organic, inorganic and microbial pollutants. As a result, it is quite challenging to treat these effluents by using only one treatment process. A combining approach is generally required to treat efficiently these wastewaters and comply with the discharge standards. In this present study, electrocoagulation (EC) and biofiltration (BF) processes were sequentially used to treat landfill leachate. EC process has been able to remove 37 ± 2% of the initial total COD. A fractionation of organic compounds showed that EC was particularly efficient to remove insoluble COD and humic acids. In addition, other pollutants such as turbidity, true color, Zn and phosphorus were significantly reduced by EC with 82 ± 2.7%, 60 ± 13%, 95 ± 2.6% and 82 ± 5.5% of removal respectively. The subsequent treatment by BF process led to completely removal of ammonia pollution (>99% of NH4 removal) and a partial removal of dissolved organic compounds (42 ± 7% of COD removal). The hybrid process EC/BF could form the basis of a process capable of removing organic and inorganic pollutants from many refractory wastewaters (mature landfill leachates, industrial and municipal wastewaters).